Magnetic/plasmonic MnFe2O4/Au nanoparticles covered with lipid bilayers for applications in thermotherapy - Matos, Joana Isabel Oliveira Gomes de (2017)
In this work, three different types of magnetic/plasmonic nanoparticles were prepared: core-shell nanoparticles with a manganese ferrite core and a gold shell; plasmonic gold nanoparticles decorated with magnetic nanoparticles of manganese ferrite; and magnetic nanoparticles of manganese ferrite decorated with plasmonic gold nanoparticles. The structural, spectroscopic and magnetic properties of these nanoparticles were evaluated. In order to further develop applications in cancer therapy, the prepared mixed nanoparticles were covered with a lipid bilayer. The local heating capability of these nanosystems was tested through the quenching of rhodamine fluorescence incorporated in the lipid layer.